Design, Formulation, and Assessment of Pharmaceutical Co-Crystals on Antipsychotic Agent - Mayuri N. Pole (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: This study designed, developed, and evaluated long-acting olanzapine (OLA) formulations for schizophrenia and bipolar disorder therapy through parenteral route. The formulations were tested for appearance, particle size, drug entrapment effectiveness, surface morphology, pH, 15- and 30-day in vitro drug release, histopathology, and animal pharmacokinetics. Materials and Methods: Accelerated and controlled stability testing for the optimized final formulation lasted 6 and 12 months. The optimized OLA long-acting extendedrelease injectable microspheres formulation had a particle size of 37.80 ± 1.10 μm, 98.55 ± 1.28% drug entrapment efficiency, and 40.6 ± 7.14% and 98.9 ± 3.24% drug release at 15 and 30 days, respectively. Results: All batches were particle-free visually. All examined batches had pH levels ranging from 4.50 ± 0.05 to 6.22 ± 0.11. Compared to the positive control, OLA formulation histopathology shows no epithelial cell damage. The long-acting extended-release microsphere formulation of OLA demonstrated higher Cmax (49.4 ± 1.58 ng/mL) and Tmax (14.64 ± 3.49 days) compared to oral drug suspension (1.20 ± 0.32 days) and T1/2 (25 ± 2.96 days) compared to oral drug suspension (3.95 ± 0.59 days). The optimized long-acting extended-release injectable OLA microsphere formulation proved stable after 6 months in accelerated and 12 months under controlled conditions. Conclusion: In conclusion, quality by design-based development of long-acting extended-release injectable OLA microsphere in situ gel formulations showed plasma drug availability at controlled release for 30 days and can overcome the oral route administration drawback of these drugs.